AI-POWERED LEARNING MODELS TO FOSTER STUDENT CREATIVITY IN SOCIAL STUDIES EDUCATION - Suroiya, Mufatihatus (JURNAL SOCIUS, 2025)
In the face of technological advancements in the industry 4.0 era and the transition toward the industry 5.0 era, the education sector must innovate in designing learning models that are not only effective but also relevant. Artificial Intelligence (AI) offers new opportunities for creating learning models that are more interactive, adaptive, and innovative. The purpose of this research is to explore the utilization of AI in developing Social Studies learning models that can enhance students' creativity. By integrating AI technologies such as learning chatbots, data visualization, interactive simulations, and automated assessment systems, the goal is to create a more interactive, contextual learning environment that supports creativity development. This study employs a mixed-methods approach with an action research design. The results indicate that the AI-based learning model developed significantly improved students' creativity compared to the control group that used traditional methods. The AI applied in Social Studies learning encourages students to enhance their creative thinking skills, problem-solving abilities, and 21st-century skills such as collaboration, communication, and digital literacy.